The Distributional Impact of Taxes and Transfers in Poland - Goraus, Karolina; Inchauste, Gabriela (World Bank, Washington, DC, 2016)
This paper assesses the impact of fiscal policy on the incidence, depth, and severity of poverty, and examines whether there is room for an increased role for fiscal policy in improving the wellbeing of the poor. The results show that the combined effect of taxes and social spending helped substantially to reduce poverty and inequality in Poland in 2014, in line with other European Union countries, with most of the reduction largely being achieved by pensions. However, in cash terms, households beginning in the second decile were net payers to the treasury in 2014, as the share of taxes paid exceeded the cash benefits received for all but the poorest 10 percent of the population. Although the Polish fiscal system in 2014 had the capacity to redistribute, it had a relatively weak capacity to reduce poverty given the resources at its disposal, and this was especially true for families with children. Microsimulations of the introduction of the Family 500+ program in 2016 show the redistributive and poverty reduction impacts of the new program, even after taking into account the potential increase in indirect taxes. Finally, alternative reforms of the tax-free allowance are considered, and estimates of their likely impact on poverty, inequality, and the potential fiscal cost are presented. The simulations show that there are potential efficiency gains from further targeting each of these new initiatives.